CHALLENGES OF THE PSYCHOLOGIST'S WORK AT CREAS DE CAMALAÚ/PB – EXPERIENCE REPORT - dos Santos Oliveira, Renata; Coelho de Lisle Júnior, Leconte (Health and Society, 2024)
The Specialized Reference Center for Social Assistance is a state unit that offers specialized and continuous services to individuals in situations of threat or violation of rights such as: psychological, physical, sexual violence and compliance with socio-educational measures. The objective is to present the challenges of the psychologist in the scope of CREAS. As a method, the experience of a psychologist at the Specialized Reference Center for Social Assistance (CREAS), in the municipality of Camalaú, PB, is reported. With the results, it was possible to observe the reality of the psychology professional who chooses to act in the provision of SUAS services. As a conclusion, it is considered that social assistance represents an indispensable field of work to discuss the role of the psychologist in the face of challenges.